Answeri got u my boy
Explanation:
it is
implifying
4x + 6y + -3 = 0
Reorder the terms:
-3 + 4x + 6y = 0
Solving
-3 + 4x + 6y = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '3' to each side of the equation.
-3 + 4x + 3 + 6y = 0 + 3
Reorder the terms:
-3 + 3 + 4x + 6y = 0 + 3
Combine like terms: -3 + 3 = 0
0 + 4x + 6y = 0 + 3
4x + 6y = 0 + 3
Combine like terms: 0 + 3 = 3
4x + 6y = 3
Add '-6y' to each side of the equation.
4x + 6y + -6y = 3 + -6y
Combine like terms: 6y + -6y = 0
4x + 0 = 3 + -6y
4x = 3 + -6y
Divide each side by '4'.
x = 0.75 + -1.5y
Simplifying
x = 0.75 + -1.5y